Clinico-mycological study of onychomycosis in children from a tertiary care center - Shazia Jeelani; Audil Mohmad Lanker; Nasir Jeelani; Qazi Masood Ahmed; Tawhida Fazili; Humera Bashir (Wolters Kluwer Medknow Publications, 2016)
Introduction: Onychomycosis is rare in children as compared to adults and hence the presence of any nail changes in children needs careful examination and carrying out proper diagnostic tests to cure this treatable cause of dystrophic nails. Aim: The study was undertaken to study in detail the clinico-mycological aspects of onychomycosis in children. Materials and Methods: A prospective hospital-based cross-sectional study was done on ninety children with a strong clinical suspicion of onychomycosis during a period of 2 years. All the children were subjected to three diagnostic tests, namely direct microscopy, fungal culture, and histopathological examination using periodic acid Schiff staining (HPE-PAS). Results: Distal and lateral subungual onychomycosis is the most common type (82%), and toe nails (57.78%) are more commonly involved than fingernails. Direct microscopy yielded results in 62%, culture in 64%, and HPE-PAS in 71.1%. Dermatophytes were the most common group of organisms isolated (58%) with Trichophytonmentagrophytes as the most common isolate (31%). However, nondermatophytic molds and Candida species also accounted for 25% and 17% of the culture positive cases in children. Conclusion: As children <18 years constitute one-third of our population, we suggest the need for careful evaluation of onychomycosis in this subgroup.